Breastfeeding performance index and associated factors among children aged 0–6 months in Ethiopia: Analysis of the 2019 Ethiopia Mini Demographic and Health Survey - Gessese, Getachew Tilahun; Woldeamanuel, Berhanu Teshome; Demie, Takele Gezahegn; Diriba Biratu, Tolesa; Handebo, Simegnew (Frontiers in Nutrition, 2022)
Background: Infants under the age of 6 months are commonly affected by malnutrition globally. The higher the breastfeeding performance index, the greater the advantage of breastfeeding will be. However, there is a lack of literature in the context of Ethiopia. Therefore, this study is aimed at investigating the magnitude and determinants of the breastfeeding performance index score among mothers of children under the age of six months in Ethiopia. Methods: This study was conducted using the 2019 Ethiopia Mini Demographic and Health Survey dataset. A stratified, two-stage cluster sampling technique was used in the study. The survey data were weighted using the "svy" function in STATA version 16. Descriptive statistics, bivariable and multivariable logistic regression were employed in the analysis. Adjusted odds ratio (AOR) with a 95% confidence interval (CI) was reported. The results were considered statistically significant if the p-value was <0.05. The goodness of fit of the model was checked using the Hosmer–Lemeshow test. Results: A total of 4273 mothers with children under the age of six months were included in the analysis. Our analysis revealed that the prevalence of low breast feeding performance index was 79.05% (95% CI: 78.01, 81.59). A unit increase in child age (AOR = 11.56; 95 % CI 6.97, 19.17), the richest wealth quintile (AOR = 2.76; 95 % CI 1.18, 6.5), a higher level of education (AOR = 5.41; 95 % CI 2.08, 14.05), being married or living with partner (AOR = 2.73; 95 % CI 1.18, 6.27), being women from Somali (AOR = 5.11; 95 % CI 2.08, 12.56), Afar (AOR=3.03; 95% CI 1.16, 7.91), Oromia (AOR=1.88; 95% CI 1.03, 3.41), and Diredawa city administration (AOR= 2.89; 95% CI 1.04, 8.07), and antenatal care visit (AOR= 2.05; 95% CI 1.31, 3.19) were positively associated with low breastfeeding performance index. Conclusion: The prevalence of low breastfeeding performance index was found to be high. Hence, the findings of the study suggest the need to target interventions aimed at improving breastfeeding performance towards mothers with higher socio-economic and demographic status and educational status. Antenatal care clients are among the targets of the intervention.